Problems Book to accompany Mathematics for Economists, Chapter 1: Matrix Algebra - Tamara Todorova (Problems Book to Accompany Mathematics for Economists, 2010)
In highly mathematical courses, it is a truism that students learn by doing, not by reading. Tamara Todorova's Problems Book to Accompany Mathematics for Economists provides a life line for students seeking an extra leg up in challenging courses. Beginning with college-level mathematics, this comprehensive workbook presents an extensive number of economics focused problem sets, with clear and detailed solutions for each one. By keeping the focus on economic applications, Todorova provides economics students with the mathematical tools they need for academic success. For years, Professor Todorova has taught microeconomic courses to economists and non-economists, introduced students to new institutional economics as a modern trend in economics, and taught quantitative methods and their application to economic theory, marketing, and advertising.
Keywords: 330